Pendampingan Pemasaran Berbasis Digital Bagi Pelaku Usaha Otomotif Pada UD. R3 Jaya Mobil Sebagai Strategi Peningkatan Daya Saing di Era Ekonomi Digital - Samsinar Samsinar; Itsna Muflikhah; Yustika Jauhari; Nurul Maghfirah Surianto; Risa Rukmana (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This Community Service Activity aims to increase MSME literacy in utilizing digital/social media in promoting products sold to increase branding and product sales. UD. R3 Jaya Mobil, as one of the automotive business actors engaged in vehicle sales and maintenance services in the Makassar area, faces similar challenges. Based on initial observations, this business has quite large market potential due to its strategic location and has regular customers. The Digital Marketing Assistance Activity for Automotive Business Actors has been successfully implemented with positive achievements. Through a participatory and applied approach, this activity is able to increase knowledge, skills, and awareness of partners regarding the importance of implementing digital marketing strategies in developing businesses. In addition, this activity also encourages business actors to be more adaptive to developments in information technology which is a main characteristic of the digital economy era